1977
DOI: 10.1113/jphysiol.1977.sp011952
|View full text |Cite
|
Sign up to set email alerts
|

Slow mechanism for sodium permeability inactivation in myelinated nerve fibre of Xenopus laevis.

Abstract: SUMMARY1. Single myelinated nerve fibres were isolated and the nodal currents were recorded under potential clamp conditions. The effect of membrane potential on the Na permeability (PNa) mechanism was analysed.2. The available PNa increased slowly during negative polarization of the membrane. The time course of this change was about 103 times slower than the time course of the mechanism for the usual PNa inactivation (h-system). The slow PNa changes could be distinguished from changes in h because of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…In lobster (Narahashi, 1964), squid (Adelman & Palti, 1969;Rudy, 1978), and Myxicola giant axons (Schauf, Pencek & Davis, 1976;Rudy, 1981), as well as in myelinated nerve (Peganov, Khodorov & Shishkova, 1973;Brismar, 1977), and in frog skeletal muscle (Collins et al 1982), cell membrane depolarization maintained over hundreds of milliseconds results in the reversible decline of Na current. Though slower than the rapid inactivation occurring during a single action potential (Hodgkin & Huxley, 1952), these processes are still 2-3 orders of magnitude faster than the effects described here.…”
Section: Resultsmentioning
confidence: 99%
“…In lobster (Narahashi, 1964), squid (Adelman & Palti, 1969;Rudy, 1978), and Myxicola giant axons (Schauf, Pencek & Davis, 1976;Rudy, 1981), as well as in myelinated nerve (Peganov, Khodorov & Shishkova, 1973;Brismar, 1977), and in frog skeletal muscle (Collins et al 1982), cell membrane depolarization maintained over hundreds of milliseconds results in the reversible decline of Na current. Though slower than the rapid inactivation occurring during a single action potential (Hodgkin & Huxley, 1952), these processes are still 2-3 orders of magnitude faster than the effects described here.…”
Section: Resultsmentioning
confidence: 99%
“…3, which gave p = 0-26. It is concluded that the initial current was mainly a Na current (denoted INa below), but that the Na selectivity was lower than in the frog node (p 0-05, Frankenhaeuser & Moore, 1963b;p=008, Hille, 1975 (Drouin & Neumcke, 1974;Brismar, 1977), which causes a potential drop outside the membrane depending on the inward current amplitude. It may be concluded from Fig.…”
Section: Membiane Currentsmentioning
confidence: 99%
“…2 that there is a mechanism for PNo inactivation in the rat node that resembles the h-system in squid and frog nerve (Hodgkin &;Huxley, 1952b;Frankenhaeuser, 1959Frankenhaeuser, , 1960 (Brismar, 1977) the time course consisted of a rapid initial phase that was fitted by an exponential time constant (as) and a slow variation ia peakINc that was observed as a deviation from the steady state at long lasting conditioning pulses. The rapid inactivation system (h) could generally be distinguished from the slow inactivation changes, because the time courses were sufficiently different.…”
Section: Pna Inactivation Systemmentioning
confidence: 99%
“…Studies in nerve (Adelman & Palti, 1969;Chandler & Meves, 1970;Peganov, Khodorov & Shishkova, 1973;Fox, 1976;Schauf, Pencek & Davis, 1976;Brismar, 1977;Chiu, 1977;Rudy, 1981;Sigworth, 1981;Collins, Rojas & Suarez-Isla, 1982) and in muscle (Reuter, 1968;Brown, Lee & Powell, 1981;Almers, Stanfield & StUhmer, 1983;Patlak & Oritz, 1985; Ruff, Simoncini & Stiihmer, 1987;Simoncini & Stiihmer, 1987) have shown that sodium channels in these excitable tissues display multiple components of inactivation, components that can be distinguished by their different kinetics. In this paper we show that sodium channels in mammalian Schwann cells, cells which are not generally regarded as excitable, also show kinetically distinct components of inactivation.…”
Section: Introductionmentioning
confidence: 99%